Mesenchymal stem cell-derived conditioned medium protects vascular grafts of brain-dead rats against in vitro ischemia/reperfusion injury - Korkmaz-İçöz, Sevil; Zhou, Pengyu; Guo, Yuxing; Loganathan, Sivakkanan; Brlecic, Paige; Radovits, Tamás; Sayour, Alex Ali; Ruppert, Mihály; Veres, Gábor; Karck, Matthias; Szabó, Gábor (Stem cell research & therapy, 2021)
Brain death (BD) has been suggested to induce coronary endothelial dysfunction. Ischemia/reperfusion (IR) injury during heart transplantation may lead to further damage of the endothelium. Previous studies have shown protective effects of conditioned medium (CM) from bone marrow-derived mesenchymal stem cells (MSCs) against IR injury. We hypothesized that physiological saline-supplemented CM protects BD rats’ vascular grafts from IR injury.